Multi platform online patient monitoring system - Murat Demirtaş; Gökalp Tulum; Mehmet Sağbaş; Umut Ayten (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2018)
In this study, patient monitoring system whichenables instant recording the data from biomedical sensor (ECG, heart rate,temperature, movement, etc.) is developed. The main structures of the proposedsystem consist of biomedical sensors, ATmega microcontroller and IEEE 802.11Wi-Fi module. The signals, obtained from the biomedical sensors, converted todigital data and transferred to the server by the Wi-Fi module. In this way,the biomedical data’s are delivered to the medical staffs that are connected tothe system with mobile and desktop devices. Moreover, in case of emergency thesystem could alert the relevant departments with embedded systems and serversoftware.